2019
DOI: 10.1111/jofo.12304
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the breeding biology of Rufous Potoos (Nyctibius bracteatus) in lowland Ecuadorian Amazon

Abstract: Five species of potoos occur in Ecuador, with Rufous Potoos (Nyctibius bracteatus) being one of the least known. We monitored a nest site of Rufous Potoos in a lowland forest in the Ecuadorian Amazon and provide information about the behavior of a nestling and one or more adults. Observations were conducted opportunistically from 10 August to 10 September 2018, and an infrared heat-and-motion activated camera was used to monitor the nest site from 11 September to 13 November 2018. We recorded 2006 10-s videos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The adult also rocked when a group of monkeys (Brown Capuchin Sapajus apella) passed over the nest and when an understorey mixed-species flock came close. Similar behaviour was observed by Vinueza-Hidalgo et al (2019) in Ecuador, with the bird adopting an alarm posture (slow rocking motion) when approached too closely. On 19 October the chick was alone on the nest for the first time (Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The adult also rocked when a group of monkeys (Brown Capuchin Sapajus apella) passed over the nest and when an understorey mixed-species flock came close. Similar behaviour was observed by Vinueza-Hidalgo et al (2019) in Ecuador, with the bird adopting an alarm posture (slow rocking motion) when approached too closely. On 19 October the chick was alone on the nest for the first time (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Rufous Potoo lays a single egg sited atop a smaller tree stump (Cohn-Haft 1989, Cisneros-Heredia 2006, Ingels et al 2008. A recent study suggested that reproductive ecology and behaviour recall those of other potoos, but reinforced the need for additional studies (Vinueza-Hidalgo et al 2019). Here we present novel data on the species' breeding, based on observations at three nests in central Amazonian Brazil, and discuss egg morphology, parental care, and nestling appearance, development and behaviour.…”
mentioning
confidence: 99%